1995
DOI: 10.1038/ng0595-28
|View full text |Cite
|
Sign up to set email alerts
|

A lipoprotein lipase mutation (Asn291Ser) is associated with reduced HDL cholesterol levels in premature atherosclerosis

Abstract: A reduction of high density lipoprotein cholesterol (HDC) is recognized as an important risk factor for coronary artery disease (CAD). We now show in approximately 1 in 20 males with proven atherosclerosis that an Asn291Ser mutation in the human lipoprotein lipase (LPL) gene is associated with significantly reduced HDL levels (P = 0.001) and results in a significant decrease in LPL catalytic activity (P < 0.0009). The relative frequency of this mutation increases in those patients with lower HDL cholesterol le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
144
3
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(162 citation statements)
references
References 33 publications
14
144
3
1
Order By: Relevance
“…Both genetic as well as acquired deficiencies of LPL are associated with high TG and low HDL levels in human and animal models (17,29). More recently, two mutations in the LPL gene were found to be associated with low plasma HDL-C levels (47,48). Our findings in the L2-MCK and L0-MCK mice contradict the current thinking of a simple relationship whereby increased LPL causes increased lipolysis, reduced TG, and increased HDL-C levels.…”
Section: Discussioncontrasting
confidence: 57%
“…Both genetic as well as acquired deficiencies of LPL are associated with high TG and low HDL levels in human and animal models (17,29). More recently, two mutations in the LPL gene were found to be associated with low plasma HDL-C levels (47,48). Our findings in the L2-MCK and L0-MCK mice contradict the current thinking of a simple relationship whereby increased LPL causes increased lipolysis, reduced TG, and increased HDL-C levels.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies of lipid lowering drugs have shown that vascular function is improved by LPL-mediated generation of free fatty acids (10). Furthermore, humans with mutations in the promoter region of LPL are at increased risk for developing atherosclerosis (11). In macrophages, LPL is known to mediate increased uptake of lipoproteins and to induce TNF-␣.…”
mentioning
confidence: 99%
“…This yields P 2 and H 2 alleles in the presence of restriction sites. Coding sequence polymorphisms in exon 2 (Asp 9 -Asn), 6 (Asn 291 -Ser) and 9 (Ser 447 -Ter) were genotyped as previously described [24,32,38], yielding alleles G and A, R 1 and R 2 , and C and G respectively in the presence and absence of the restriction sites (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…We and others have previously found that genetic variants of LPL relate to dyslipidaemia and atherosclerosis, including concentrations of triglycerides [24,25,26,27,28,29], high density lipoprotein cholesterol (HDL-C) [24,25,30,31,32], and total cholesterol [25,29,31], development [24,25,33] and severity [24,26] of coronary artery disease, familial combined hyperlipidaemia [34,35] and familial chylomicronaemia [36]. Recently, no relationship was found between an exonic LPL polymorphism and Type I diabetic nephropathy [37], although a potent effect of total cholesterol, triglycerides and apo-B was noted on DN.…”
mentioning
confidence: 99%